PEMANFAATAN ELECTRONIC GOVERNMENT UNTUK MENDUKUNG REFORMASI BIROKRASI PEMERINTAH PADA PEMERINTAHAN KOTA SEMARANG - Nabila Khoirun Nissa; Suwanto Adhi (Journal of Politic and Government Studies, 2018)
This research paper aims to explain the use of electronic government as one of the supporters of government bureaucracy reform in the administration of Semarang City. This type of research is analytical desktiptif through a qualitative approach. Sources of data in this study were obtained from interviews with resource persons and archives / documents relating to research. The sampling technique uses purposive sampling. Data collection techniques used in this research are interviews, observations, and documents. Based on the results of the study it can be seen that electronic government in the Semarang City Government is very well utilized so as to improve the quality of its government. The emergence of new innovations made to provide better services for the community and its own employees. Where it is expected that with all the affairs of the government apparatus facilitated by the application that has been made, the government apparatus can also facilitate all matters needed from the community. The inhibiting factor encountered was the lack of work motivation that emerged in employees, application management was still focused on their respective duties, and there was still a lack of competent employees. For the successful use of electronic government in reforming the government bureaucracy, recommendations are given for activities that can increase motivation from within the government apparatus, integrity between applications in order to improve service performance, and improve the quality of the government apparatus in carrying out tasks.Keywords: e-government, public service, quality of government apparatus, Semarang City government.